Effectiveness of an autism spectrum disorder screening and follow-up training program for primary health care professionals in Türkiye - Gürbüz Özgür, Börte; Aksu, Hatice; Eser, Erhan (The Turkish Journal of Pediatrics, 2025)
Background. Autism spectrum disorder (ASD) screening and follow-up programs are implemented in all provinces in Türkiye as part of the National Action Plan for Individuals with ASD. Primary health care professionals are trained regarding ASD by child and adolescent psychiatrists, aiming to ensure that risky children are diagnosed and referred earlier and diagnosed in early childhood. The aim of this study is to objectively evaluate the effectiveness of an ASD training program provided to primary healthcare professionals. Methods. Three hundred and three individuals consisting of family physicians and family healthcare workers (FHW) who participated in the ASD training program were recruited in the study in the Muğla province of Türkiye. The Knowledge About Childhood Autism Among Health Workers Questionnaire (KCAHW) was completed by all participants before and after the training. Results. The mean total KCAHW scores pre- and post-training were 13.12±3.14 and 16.48±2.02, respectively. There was a statistically significant difference in Domains 1, 2, 3, and 4 and the total scores pre- and post-training (p